A Brief Report on Reviews of Existing Creative Art–Based Interventions in Dementia Care From 2010–2020 - Manji, Irfan; Fallavollita, Pascal (Frontiers in Aging, 2022)
The following brief report provides an overview of previously published reviews in the context of creative arts-based interventions for persons with dementia. A total of 22 review articles were identified and summarized. Next steps are suggested for future studies that may wish to a) develop a new review, or b) create new studies filling in the gaps identified by the authors in this report.